Analysis of the Cinapel Bridge’s Construction Operations using Simulation - Abduh, Muhamad; Halvireski, Siska; Delfani, Catherine; Irfanto, Ryobi; Wirahadikusumah, Reini D. (IPTEK Journal of Proceedings Series, 2017)
Simulation has been well known as an effective technique that enables planning and analysis of a construction operation to be performed in advance anticipating problems of efficiencies that would occur in the implementation phase. Therefore, simulation technique could be used to design resources associated with a construction operation to be optimal and to analyze an ongoing operation to be evaluated and refined. This paper discusses the use of simulation to analyze several construction operations, i.e., bored piles, pile caps, piers, and girders, that will be used in building the Cinapel’s Bridge at the Cisumdawu Toll Road Project. The simulation using WebCYCLONE was utilized to determine the most optimal resources needed in each construction operation; resources needed to gain the highest productivity and the lowest wastes. Data of each operation for simulation were gathered from the field, as well as opinions from the practitioners related to the project. The results of the simulation are presented and recommendations are made for the contractor to refine the on-going construction operations as well as to design construction operations before the implementation in the fields.